Axial compressive behaviour and confinement effect of round-ended rectangular CFST with different central angles. (1st April 2022) - Ren, Zhigang; Wang, Dandan; Li, Peipeng
Abstract: This paper proposes a novel concept of 'central angle' to extend cross-section design of round-ended rectangular concrete-filled steel tube (RRCFST). Axial compressive behaviour and confinement mechanism of RRCFST stub columns are experimentally and numerically researched, including effects of central angle θ of round ends, aspect ratio κ of middle rectangular part, cross-sectional type, steel wall-thickness t . The results show that local buckling and shear failure of core concrete usually occur. The θ and κ can clearly describe the cross-sectional geometrical characteristics of RRCFST sections, as well as unifying circular and rectangular CFST. When the θ gradually changes from 0 to 180°, the round-ended confinement increases but the corner confinement reduces continuously, which results in overall confinement effect and material efficiency followed by parabolic trends. A larger κ leads to a weaker overall confinement and material efficiency, due to relatively wider unconstrained or weak constrained zones. The optimized cross-sections with θ around 60° and relatively smaller κ are recommended to design RRCFST subjected to axial compression, which contribute to good overall confinement effect, high material efficiency, high axial bearing load and ductility. A new reliable predicting analytical model for axial ultimate bearing capacity of RRCFST is proposed and validated.